Hubungan Kepercayaan Diri dan Kecemasan dengan Prokrastinasi Akademik Pada Mahasiswa Fakultas Psikologi Universitas Medan Area Angkatan 2015 & 2016 - Rukmawaty Deviana Situngkir; Risydah Fadilah; Abdul Murad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the relationship between self-confidence and anxiety with student academic procrastination. The sampling technique in this research was accidental sampling. The sample in this study amounted to 130 people. The method used in this study was a quantitative method. The instrument used was a Likert scale model questionnaire. The data collection technique used three scales, consisting of a self-confidence scale, an anxiety scale and an academic procrastination scale. The data analysis technique used was Multiple Regression. The results of this study indicate (1) There was a significant negative relationship between self-confidence and academic procrastination, where the coefficient rxly = -0.872 with p = 0.000, and (r²) = 0.760 with a contribution of 76%. (2). There was a significant positive relationship between anxiety and academic procrastination, where the coefficient rxly = 0.897 with p = 0.000, and (r²) = 0.805 with a contribution of 80.5%. (3). there was a significant relationship between self-confidence and anxiety with student academic procrastination. This was indicated by the linearity coefficient (R) = 0.900 with p = 0.000 < 0.050. and (r²) = 0.811 with a contribution of 81.1%. From these results it is known that there are still 19.9% contributions from other factors to academic procrastination